Clinical Utility of Reflex Ordered Testing for Molecular Biomarkers in Lung Cancer. (21st September 2018) - Phung, Thuy; Anand, Kartik; Cagle, Philip; Olsen, Randall; Bernicker, Eric H; Thomas, Jessica
Abstract: Background: Clinical testing of molecular biomarkers to guide therapy in non–small cell lung cancer has become routine and increasingly complex. To standardize and expedite molecular biomarker testing in these patients, our institution implemented reflex ordered testing for a group of targeted gene alterations in all newly diagnosed non–small cell lung carcinoma. The aim of our study is to evaluate the clinical utility of reflex ordered molecular testing in lung cancer. Methods: Lung adenocarcinoma specimens received for molecular testing at our institution over a 6-month period in 2017 were identified with IRB approval. Testing for the entire group of molecular biomarkers was ordered at diagnosis (reflex ordered) or specific biomarkers were tested at request of oncologists (nonreflex ordered). Reflex ordered biomarkers included EGFR, KRAS, BRAF, and ERBB2 mutations; ALK, RET, and ROS1 gene rearrangements; MET exon 14 skipping (MET14); MET gene amplification; and PDL-1 expression. Results: The cohort included 160 patients with non–small cell lung carcinoma with 49% (n = 78) males, 51% (82) females, and median age of 70 years (age range 43–90 years). There were 73% (117) Caucasians, 19% (30) African Americans, and 8% (13) Asians. Nineteen percent (31) of cases had nonreflex testing, and 81% (129) had reflex testing. The mean number of days from anatomic pathology reporting to molecular reporting was 23 days for reflex testing vs 52 days for nonreflex. Reflex testing had a higher variant detection rate than nonreflex (47% vs 19%, P < .05). Specific variant detection rates were EGFR = 13% (n = 20), KRAS = 26% (33), BRAF = 1.5% (2), ERBB2 = 0% (0), ALK = 5% (8), RET = 1.5% (2), ROS1 = 2.7% (4), MET14 = 0.8% (1), and MET amplification = 2.8% (3); 76% of cases had PD-L1 expression in <50% of tumor. Conclusions: The detection rates and types of pathogenic variants identified within our cohort were similar to those reported in literature. The mean turnaround time of molecular result reporting was significantly reduced with reflex testing. The variant detection rate was 2.5 times higher for reflex testing than nonreflex due to a larger number of genes covered on the reflex panel. These findings show that a standardized comprehensive strategy for molecular testing increases timely opportunities for personalized therapy in patients with non–small cell lung carcinoma.